(3efXeGJ GdCYeGd (B:s (3GdeaGgje hGdhXGFa (B/s - (3LhOI, eMahXs; (3GdRYHj, MSfs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2004)
(3efXeGJ GdCYeGd(B- (3fXQjGJ hCSGdjH EOGQjI MOjKI(B- (3hXjaI GdGfJGL(B- (3hXjaI GdJShjb(B- (3GdhXjaI GdeGdjI(B- (3hXjaI GdehGQO GdHTQjI(B- (3EOGQI GdehGQO(B- (3GdYdGbGJ GdYGeI(B- (3fXe GdeYdheGJ GdEOGQjI(B.s
Keywords: (3EOGQI GdCYeGds; (3GdEOGQI GdeGdjIs; (3efXeGJ GdCYeGds